Analyzing Syntaxic Errors In English Paragraph Writing - Tobing, Sarah Davina L; Azra, Tsabitha; Fahri, M. Aidyl; Ardi, Ahmad Rizky; Ismahani, Siti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This research aims to identify variations in syntactic errors that are often made by students in writing English paragraphs and to find out the types of errors that most commonly occur in students. This research adopts a qualitative descriptive approach using analytical methods. data is collected through observation and measurement, while the data collection instruments consist of observation sheets and written tests. The results of the analysis show that there are several types of errors found in student writing, namely errors in the categories of syntax and surface strategy. These errors include errors in noun phrases, verb phrases, transformations. Apart from that, types of errors were also found in the surface category, such as errors of omission, addition, form errors, sequence errors. In student writing, the most dominant syntactic errors occur in noun phrase. However, in the communicative taxonomy category, only a few errors were found, which shows that even though there are syntactic errors in phrases or sentences, the message conveyed can still be understood by the reader.